2019
DOI: 10.1007/s13197-019-04007-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of packaging methods and storage conditions on quality characteristics of flour product naan

Abstract: The quality characteristics of naan from flour products under various packaging methods stored at different temperatures (25, 4 and-20°C) for different time (0-49 days) were investigated. Packaging methods included ordinary plastic packaging (OPP), vacuum packaging (VP) and deoxygenation packaging (DP). Sensory value, acid value, moisture content and microbial count of naan during storage were evaluated. The results showed that the total demerit points of sensory of DP naan stored at 25°C had considerably lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In agreement with these results, Udomkun et al [28] found that the moisture content and a w of dried papaya packed in polyamide/polyethylene flms with 95% light transmissivity was signifcantly higher than that of aluminum laminated polyethylene flm with 0% light transmissivity during storage for 1 to 9 months. Tese may be associated with the water vapor generated by the light exposure, which increased a w of the samples in the package [29,30]. In this study, the BI of the V + LA group was signifcantly lower than that of the C at 6 m (P < 0.05).…”
Section: Resultsmentioning
confidence: 57%
“…In agreement with these results, Udomkun et al [28] found that the moisture content and a w of dried papaya packed in polyamide/polyethylene flms with 95% light transmissivity was signifcantly higher than that of aluminum laminated polyethylene flm with 0% light transmissivity during storage for 1 to 9 months. Tese may be associated with the water vapor generated by the light exposure, which increased a w of the samples in the package [29,30]. In this study, the BI of the V + LA group was signifcantly lower than that of the C at 6 m (P < 0.05).…”
Section: Resultsmentioning
confidence: 57%
“…A non‐significant ( p > 0.05) change in fat, protein, ash, and crude fiber content of the stored flatbreads was observed (data not reported) (Zhao et al, 2019). The mean values for color coordinates ( L *, a *, and b *) of all enriched breads showed a significant ( p < 0.05) change during storage.…”
Section: Resultsmentioning
confidence: 98%
“…A non-significant (p > 0.05) change in fat, protein, ash, and crude fiber content of the stored flatbreads was observed (data not reported) (Zhao et al, 2019). The mean values for color coor-…”
Section: Ta B L Ementioning
confidence: 86%
“…Although packaging has no direct relationship with production, storage, marketing, and distribution, it plays an important role in the safety and quality of the product after it reaches consumers [2]. Bottled oxygen can increases the rate of oil oxidation and the growth of microorganisms [15].…”
Section: Introductionmentioning
confidence: 99%